Eksplorasi Teoritis Pendidikan Ekonomi Hijau dan Inovasi Mahasiswa terhadap Energi Terbarukan - Nurwahida Nurwahida; Sri Hutami Adiningsih S (Micronic: Journal of Multidisciplinary Electrical and Electronics Engineering, 2025)
The transformation towards sustainable development demands a paradigm shift in economic education, from a conventional approach to a green approach that emphasizes the harmony between economic growth and environmental sustainability. This article aims to theoretically explore the relationship between green economic education and student innovation in the development of renewable energy technology. This study was conducted through a qualitative approach with a literature review method, reviewing scientific literature from 2020 to 2025 that is relevant to the theme. The results of the exploration show that green economic education has a strategic role in shaping environmental awareness, green entrepreneurship literacy, and encouragement of sustainable innovation. Student innovation in renewable energy is not only influenced by the availability of technology, but also by the understanding of sustainable economic values ​​obtained from the learning process. Therefore, green economic education in higher education needs to be designed contextually and interdisciplinary in order to be able to develop students' critical, creative, and collaborative competencies. This study provides a theoretical contribution to the development of economic education curriculum and encourages the strengthening of innovation culture in the campus environment.